PHA composition with low odor and high paper-plastic composite strength and preparation method thereof
By adding natural fibers and polymer-containing materials to the PHA composition and using rheology modifiers, the odor and bonding strength of PHA coating paper cups is solved, and the composite strength of low odor and high paper plastics is achieved, and the material is improved environmentally friendly and mechanical properties.
Patent Information
- Application Number
- CN202411505179.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing PHA coating paper cups will produce bad odors during use, especially when they are filled with hot water. The adhesive strength between the paper cup and the PHA coating layer is not high enough, which affects the sealing, barrier and heat sealing performance of the product.
Using a low odor, high paper-plastic composite strength PHA composition, including polyhydroxyalkanoate, natural fiber, activated carbon, X-type molecular sieve, oxazoline homopolymer, coupling agent and rheology modifier, through specific Treatment and mixing methods improve the performance of the material.
It reduces irritating odor, improves the biodegradability, thermal stability and UV resistance of the material, enhances mechanical and processing properties, and at the same time improves the adhesion strength between the paper cup and the coating layer, reducing its impact on the environment.
Smart Images

Figure CN119242006A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester materials, and in particular to a PHA composition with low odor and high paper-plastic composite strength and a preparation method thereof. Background Art
[0002] PHA composition, namely polyhydroxyalkanoate, is a natural polyester synthesized by microorganisms. It is biodegradable and biocompatible, and therefore has broad application prospects in the fields of medicine, packaging, agriculture, and biomaterials. At the same time, PHA composition also has great application potential as a coating layer in paper products.
[0003] The currently developed PHA coated paper cups will produce an unpleasant odor during use, especially when containing hot water or food at a higher temperature, the odor will be more obvious. In addition, the bonding strength between the existing paper cups and the PHA coating layer is not high enough, which affects the sealing, barrier and heat sealing properties of the product.
[0004] In view of the above technical defects, a solution is now proposed. Summary of the invention
[0005] The object of the present invention is to provide a PHA composition with low odor and high paper-plastic composite strength and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] In order to achieve the above-mentioned object, the present invention adopts the following technical scheme: a low-odor high-paper-plastic composite strength PHA composition and a preparation method thereof, wherein the low-odor high-paper-plastic composite strength PHA composition comprises the following components by weight: 95-120 parts by weight of polyhydroxyalkanoate, 40-80 parts by weight of filler, 5-80 parts by weight of polymer-containing material, 5-10 parts by weight of coupling agent, 5-25 parts by weight of hydrochloric acid, 4-10 parts by weight of rheology modifier, 5-10 parts by weight of cellulase, 3-10 parts by weight of pectinase, and 80-180 parts by weight of distilled water;
[0007] The filler comprises one or a mixture of two or more of wood fiber, bamboo fiber, flax fiber and jute fiber;
[0008] The polymer-containing material includes one or a mixture of two or more of activated carbon, X-type molecular sieve and oxazoline homopolymer;
[0009] The coupling agent is specifically vinyltrimethoxysilane;
[0010] The polyhydroxyalkanoate is poly 3-hydroxybutyrate co-3-hydroxyhexanoate;
[0011] The rheology modifier includes one or a mixture of two or more of xanthan gum, agar gum, polyurethane, epoxy resin, polyethylene glycol, glycerol and triacetin.
[0012] Furthermore, the processing method includes:
[0013] Step 1: Preliminary treatment of fillers: clean wood fiber, bamboo fiber, flax fiber and jute fiber with purified water, drain the water, and after air-drying for a period of time, chop the wood fiber, bamboo fiber, flax fiber and jute fiber respectively, and mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber in proportion to obtain a preliminary filler mixture;
[0014] Step 2, enzymatic hydrolysis of filler: add the preliminary filler mixture and distilled water to a sand mill in proportion, mix, beat and grind for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat and stir for a period of time to obtain a mixed solution 2;
[0015] Step 3, filler modification reaction: Add the mixed solution 2 and the coupling agent into a reaction container in proportion to obtain a mixed solution 3, slowly add hydrochloric acid to the mixed solution 3 while stirring, preset a target pH value, and use a pH meter to monitor the pH value of the mixed solution 3. When the pH value of the mixed solution 3 reaches the target pH value, stop adding hydrochloric acid, heat and keep warm for a period of time to obtain a mixed solution 4;
[0016] Step 4, preparing a filler mixture: spreading the mixed solution 4 on a tray, and placing it in an oven to dry for a period of time to prepare a filler mixture;
[0017] Step 5: Preliminary treatment of polymer-containing materials: Add activated carbon and distilled water into a reaction vessel, heat to boiling and keep warm for a period of time, then cool for a period of time and drain the water, and dry for a period of time to obtain impurity-removed activated carbon;
[0018] The X-type molecular sieve is washed with distilled water, and then the water is drained and dried for a period of time to obtain the impurity-removed X-type molecular sieve;
[0019] Add impurity-removing activated carbon and impurity-removing X-type molecular sieve into a grinder according to a certain proportion and grind for a period of time to obtain a preliminary material mixture 1;
[0020] Step 6, preparing a material mixture: preheating the oxazoline homopolymer and keeping it warm, then slowly adding the preheated oxazoline homopolymer to the preliminary material mixture 1, stirring and mixing thoroughly to prepare the preliminary material mixture 2, and drying by hot air drying for a period of time to remove moisture to prepare the material mixture;
[0021] Step 7, preparing the PHA composition: adding the polyhydroxyalkanoate, filler mixture and material mixture into the twin-screw extruder from the main feed port in proportion for melt mixing, and adding a rheology modifier to the feeding side of the extruder to improve the material processing performance, and cooling and pelletizing the melt extruded from the die to obtain the desired PHA composition.
[0022] Furthermore, in the step 1, the air-drying time is 3 hours, and the air-drying temperature is 25-50° C.;
[0023] In the step 1, the mass ratio of wood fiber, bamboo fiber, flax fiber and jute fiber is 20:1-20:1.5-15:0.1-12:12.
[0024] Furthermore, in the step 2, the mass ratio of the preliminary filler mixture to distilled water is 20:1-50;
[0025] In the step 2, the mass ratio of the mixed solution 1, cellulase and pectinase is 50:1-5:1-5;
[0026] In the step 2, the stirring speed is 500-700 r / min, the temperature of the enzymatic hydrolysis reaction is 40-70° C., and the time of the enzymatic hydrolysis reaction is 2-24 h.
[0027] Furthermore, in the step 3, the mass ratio of the mixed solution 2 to the coupling agent is 20:0.1-5;
[0028] In the step 3, the preset target pH value is 3.5, and the stirring speed is 600-800 r / min;
[0029] In the step 3, the temperature is heated to 80-100° C. and kept warm for 5-8 hours.
[0030] Furthermore, in step 4, the drying temperature is 50-80° C., and the drying time is 3-24 hours.
[0031] Furthermore, in step 5, the activated carbon is heated to 100° C. and kept warm for 0.5 to 2 hours, then cooled for 1 to 2.5 hours, cooled to a temperature of 20 to 35° C., and dried for 0.5 to 2 hours;
[0032] Dry the washed X-type molecular sieve in step 5 for 1 to 3 hours;
[0033] In the step 5, the mass ratio of the impurity-removing activated carbon to the impurity-removing X-type molecular sieve is 3-12:7-20, and the grinding is performed for 0.1-2.5 hours until the mixture is ground to 300 meshes.
[0034] Furthermore, in step 6, the oxazoline homopolymer is preheated to 50-60° C. and kept warm for 1-2.5 hours;
[0035] In step 6, the stirring speed is 800-1200 r / min, the stirring temperature is 50-80° C., and the stirring time is 0.5-3 h;
[0036] Drying time is 1.5 to 5 hours, and the drying temperature is 80 to 120°C.
[0037] Furthermore, in step seven, the mass ratio of the polyhydroxyalkanoate, the filler mixture and the material mixture is 50:5-27:7-15, wherein the speed of the twin-screw extruder is 300 rpm and the temperature is 150°C.
[0038] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0039] The PHA composition is added with natural fiber as filler, which can not only reduce the cost and absorb irritating odor, but also improve the biodegradability and environmental performance of the material, improve the thermal stability and UV resistance of the prepared PHA composition, and the addition of polymer-containing materials can improve the water resistance of the PHA composition, and improve its mechanical properties and processing properties;
[0040] At the same time, the addition of a rheology modifier can improve the compatibility of PHA with other polymers, thereby achieving better performance in the blend and improving the fluidity and printing accuracy of the filled composite material. The PHA composition as a coating layer not only has a low irritating odor and low impact on the environment, but also has high paper-plastic composite strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The flowchart of the preparation of the PHA composition with low odor and high paper-plastic composite strength in the present invention is shown. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] A low-odor and high-paper-plastic composite PHA composition and a preparation method thereof. The low-odor and high-paper-plastic composite PHA composition comprises the following components by weight: 95 to 120 parts by weight of polyhydroxyalkanoate, 40 to 80 parts by weight of filler, 5 to 80 parts by weight of polymer-containing material, 5 to 10 parts by weight of coupling agent, 5 to 25 parts by weight of hydrochloric acid, 4 to 10 parts by weight of rheology modifier, 5 to 10 parts by weight of cellulase, 3 to 10 parts by weight of pectinase, and 80 to 180 parts by weight of distilled water;
[0044] The filler includes one or a mixture of two or more of wood fiber, bamboo fiber, flax fiber and jute fiber;
[0045] The polymer-containing material includes one or a mixture of two or more of activated carbon, X-type molecular sieve and oxazoline homopolymer;
[0046] The coupling agent is specifically vinyltrimethoxysilane;
[0047] The polyhydroxyalkanoate is poly 3-hydroxybutyrate-co-3-hydroxyhexanoate;
[0048] The rheology modifier includes one or a mixture of two or more of xanthan gum, agar gum, polyurethane, epoxy resin, polyethylene glycol, glycerol and triacetin.
[0049] like Figure 1 As shown, the specific preparation method of the PHA composition with low odor and high paper-plastic composite strength comprises the following steps:
[0050] Step 1: Preliminary treatment of fillers: clean wood fiber, bamboo fiber, flax fiber and jute fiber with purified water, drain the water, air-dry for 3 hours at a temperature of 25-50° C., chop the wood fiber, bamboo fiber, flax fiber and jute fiber respectively, and mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber in proportion to obtain a preliminary filler mixture;
[0051] Among them, the mass ratio of wood fiber, bamboo fiber, flax fiber and jute fiber is 20:1-20:1.5-15:0.1-12:12;
[0052] Step 2, enzymatic hydrolysis of filler: add the preliminary filler mixture and distilled water to a sand mill in proportion, mix, beat and grind for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat and stir for a period of time to obtain a mixed solution 2;
[0053] The mass ratio of the preliminary filler mixture to distilled water is 20:1-50, the mass ratio of the mixed solution 1, cellulase and pectinase is 50:1-5:1-5, the stirring speed is 500-700 r / min, the temperature of the enzymatic reaction is 40-70°C, and the time of the enzymatic reaction is 2-24 hours;
[0054] Step 3, filler modification reaction: Add mixed solution 2 and coupling agent into a reaction container in proportion to obtain mixed solution 3, wherein the mass ratio of mixed solution 2 to coupling agent is 20:0.1-5, slowly add hydrochloric acid into mixed solution 3 while stirring, the stirring speed is 600-800r / min, the preset target pH value is 3.5, and the pH value of mixed solution 3 is monitored by a pH meter. When the pH value of mixed solution 3 reaches the target pH value, stop adding hydrochloric acid, heat to 80-100°C and keep warm for 5-8h to obtain mixed solution 4;
[0055] Step 4, preparing a filler mixture: spreading the mixed solution 4 on a tray, and placing it in an oven to dry for a period of time to prepare a filler mixture;
[0056] The drying temperature is 50-80°C and the drying time is 3-24h;
[0057] Step 5: Preliminary treatment of polymer-containing materials: Add activated carbon and distilled water into a reaction vessel, heat to 100°C, keep warm for 0.5-2h, then cool for 1-2.5h, cool to a temperature of 20-35°C, drain the water, and dry for 0.5-2h to obtain impurity-removed activated carbon;
[0058] The X-type molecular sieve is washed with distilled water, and then the water is drained and dried for 1 to 3 hours to obtain the impurity-free X-type molecular sieve;
[0059] Add impurity-removing activated carbon and impurity-removing X-type molecular sieve into a grinder according to a certain proportion and grind for a period of time to obtain a preliminary material mixture 1;
[0060] The mass ratio of the impurity-removing activated carbon to the impurity-removing X-type molecular sieve is 3-12:7-20, and the grinding is performed for 0.1-2.5 hours until the mesh size is 300.
[0061] Step 6, preparing a material mixture: preheating the oxazoline homopolymer to 50-60°C and keeping it warm for 1-2.5h, then slowly adding the preheated oxazoline homopolymer to the preliminary material mixture 1, stirring and mixing thoroughly to prepare the preliminary material mixture 2, the stirring speed is 800-1200r / min, the stirring temperature is 50-80°C, the stirring time is 0.5-3h, and the material mixture is dried by hot air drying method at a temperature of 80-120°C for 1.5-5h to remove moisture;
[0062] Step 7, preparing a PHA composition: adding polyhydroxyalkanoate, a filler mixture and a material mixture into a twin-screw extruder from a main feeding port in proportion for melt mixing, and adding a rheology modifier to the feeding side of the extruder to improve the material processing performance, and cooling and pelletizing the melt extruded from the die to obtain the desired PHA composition;
[0063] The mass ratio of the polyhydroxyalkanoate, the filler mixture and the material mixture is 50:5 to 27:7 to 15, and the rotation speed of the twin-screw extruder is 300 rpm and the temperature is 150°C.
[0064] Embodiment 1:
[0065] The invention provides a low-odor PHA composition with high paper-plastic composite strength and a preparation method thereof. The low-odor PHA composition with high paper-plastic composite strength comprises the following components by weight: 100 parts by weight of polyhydroxyalkanoate, 55 parts by weight of filler, 25 parts by weight of polymer-containing material, 5 parts by weight of coupling agent, 6 parts by weight of hydrochloric acid, 4 parts by weight of rheology modifier, 6 parts by weight of cellulase, 4 parts by weight of pectinase, and 150 parts by weight of distilled water. The specific preparation method of the low-odor PHA composition with high paper-plastic composite strength comprises the following steps:
[0066] Prepare a filler mixture: use pure water to clean wood fiber, bamboo fiber, flax fiber and jute fiber, drain the water, air-dry for 3 hours at an ambient temperature of 25°C, chop the wood fiber, bamboo fiber, flax fiber and jute fiber respectively, mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber in proportion to obtain a preliminary filler mixture, add the preliminary filler mixture and distilled water to a sand mill in proportion, mix and beat for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat to 55°C, and The mixture was stirred at a speed of 600 r / min for 3 h to obtain a mixed solution 2, the mixed solution 2 and the coupling agent were added into the reaction vessel in proportion to obtain a mixed solution 3, hydrochloric acid was slowly added into the mixed solution 3 while stirring, the stirring speed was 700 r / min, the preset target pH value was 3.5, and the pH value of the mixed solution 3 was monitored by a pH meter. When the pH value of the mixed solution 3 reached the target pH value, the addition of hydrochloric acid was stopped, the mixture was heated to 100°C and kept warm for 6 h to obtain a mixed solution 4, the mixed solution 4 was spread on a tray, put into an oven, and dried at a temperature of 60°C for 4 h to obtain a filler mixture.
[0067] Preparation of preliminary material mixture one: Add activated carbon and distilled water into a reaction vessel, heat to 100°C and keep warm for 2 hours, then cool for 2 hours and cool to 25°C and drain the water, dry for 1.5 hours to obtain impurity-removed activated carbon, wash the X-type molecular sieve with distilled water, then drain the water and dry for 1.3 hours to obtain the impurity-removed X-type molecular sieve, add the impurity-removed activated carbon and impurity-removed X-type molecular sieve into a grinder according to proportion, grind for 1.5 hours, and grind to 300 mesh to obtain preliminary material mixture one.
[0068] Preparation of material mixture: preheat the oxazoline homopolymer to 55°C and keep it warm for 2 hours, then slowly add the preheated oxazoline homopolymer to preliminary material mixture one, stir and mix thoroughly to obtain preliminary material mixture two, the stirring speed is 1000r / min, the stirring temperature is 70°C, the stirring time is 2.3h, and the material mixture is obtained by hot air drying at an ambient temperature of 100°C for 5 hours to remove moisture.
[0069] Preparation of PHA composition: polyhydroxyalkanoate, filler mixture and material mixture are added into a twin-screw extruder from the main feed port in proportion for melt mixing, and a rheology modifier is added to the feeding side of the extruder to improve the material processing performance, and the melt extruded from the die is cooled and pelletized to obtain the desired PHA composition, wherein the extruder barrel temperature is set to 150°C and the extruder speed is 300rpm.
[0070] Embodiment 2:
[0071] The invention provides a low-odor PHA composition with high paper-plastic composite strength and a preparation method thereof. The low-odor PHA composition with high paper-plastic composite strength comprises the following components by weight: 100 parts by weight of polyhydroxyalkanoate, 65 parts by weight of filler, 25 parts by weight of polymer-containing material, 5 parts by weight of coupling agent, 6 parts by weight of hydrochloric acid, 4 parts by weight of rheology modifier, 6 parts by weight of cellulase, 4 parts by weight of pectinase, and 150 parts by weight of distilled water. The specific preparation method of the low-odor PHA composition with high paper-plastic composite strength comprises the following steps:
[0072] Prepare a filler mixture: use pure water to clean wood fiber, bamboo fiber, flax fiber and jute fiber, drain the water, air-dry for 3 hours at an ambient temperature of 25°C, chop the wood fiber, bamboo fiber, flax fiber and jute fiber respectively, mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber in proportion to obtain a preliminary filler mixture, add the preliminary filler mixture and distilled water to a sand mill in proportion, mix and beat for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat to 55°C, and The mixture was stirred at a speed of 600 r / min for 3 h to obtain a mixed solution 2, the mixed solution 2 and the coupling agent were added into the reaction vessel in proportion to obtain a mixed solution 3, hydrochloric acid was slowly added into the mixed solution 3 while stirring, the stirring speed was 700 r / min, the preset target pH value was 3.5, and the pH value of the mixed solution 3 was monitored by a pH meter. When the pH value of the mixed solution 3 reached the target pH value, the addition of hydrochloric acid was stopped, the mixture was heated to 100°C and kept warm for 6 h to obtain a mixed solution 4, the mixed solution 4 was spread on a tray, put into an oven, and dried at a temperature of 60°C for 4 h to obtain a filler mixture.
[0073] Preparation of preliminary material mixture one: Add activated carbon and distilled water into a reaction vessel, heat to 100°C and keep warm for 2 hours, then cool for 2 hours and cool to 25°C and drain the water, dry for 1.5 hours to obtain impurity-removed activated carbon, wash the X-type molecular sieve with distilled water, then drain the water and dry for 1.3 hours to obtain the impurity-removed X-type molecular sieve, add the impurity-removed activated carbon and impurity-removed X-type molecular sieve into a grinder according to proportion, grind for 1.5 hours, and grind to 300 mesh to obtain preliminary material mixture one.
[0074] Preparation of material mixture: preheat the oxazoline homopolymer to 55°C and keep it warm for 2 hours, then slowly add the preheated oxazoline homopolymer to preliminary material mixture one, stir and mix thoroughly to obtain preliminary material mixture two, the stirring speed is 1000r / min, the stirring temperature is 70°C, the stirring time is 2.3h, and the material mixture is obtained by hot air drying at an ambient temperature of 100°C for 5 hours to remove moisture.
[0075] Preparation of PHA composition: polyhydroxyalkanoate, filler mixture and material mixture are added into a twin-screw extruder from the main feed port in proportion for melt mixing, and a rheology modifier is added to the feeding side of the extruder to improve the material processing performance, and the melt extruded from the die is cooled and pelletized to obtain the desired PHA composition, wherein the extruder barrel temperature is set to 150°C and the extruder speed is 300rpm.
[0076] Embodiment 3:
[0077] The invention provides a low-odor PHA composition with high paper-plastic composite strength and a preparation method thereof. The low-odor PHA composition with high paper-plastic composite strength comprises the following components by weight: 100 parts by weight of polyhydroxyalkanoate, 80 parts by weight of filler, 25 parts by weight of polymer-containing material, 5 parts by weight of coupling agent, 6 parts by weight of hydrochloric acid, 4 parts by weight of rheology modifier, 6 parts by weight of cellulase, 4 parts by weight of pectinase, and 150 parts by weight of distilled water. The specific preparation method of the low-odor PHA composition with high paper-plastic composite strength comprises the following steps:
[0078] Prepare a filler mixture: use pure water to clean wood fiber, bamboo fiber, flax fiber and jute fiber, drain the water, air-dry for 3 hours at an ambient temperature of 25°C, chop the wood fiber, bamboo fiber, flax fiber and jute fiber respectively, mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber in proportion to obtain a preliminary filler mixture, add the preliminary filler mixture and distilled water to a sand mill in proportion, mix and beat for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat to 55°C, and The mixture was stirred at a speed of 600 r / min for 3 h to obtain a mixed solution 2, the mixed solution 2 and the coupling agent were added into the reaction vessel in proportion to obtain a mixed solution 3, hydrochloric acid was slowly added into the mixed solution 3 while stirring, the stirring speed was 700 r / min, the preset target pH value was 3.5, and the pH value of the mixed solution 3 was monitored by a pH meter. When the pH value of the mixed solution 3 reached the target pH value, the addition of hydrochloric acid was stopped, the mixture was heated to 100°C and kept warm for 6 h to obtain a mixed solution 4, the mixed solution 4 was spread on a tray, put into an oven, and dried at a temperature of 60°C for 4 h to obtain a filler mixture.
[0079] Preparation of preliminary material mixture one: Add activated carbon and distilled water into a reaction vessel, heat to 100°C and keep warm for 2 hours, then cool for 2 hours and cool to 25°C and drain the water, dry for 1.5 hours to obtain impurity-removed activated carbon, wash the X-type molecular sieve with distilled water, then drain the water and dry for 1.3 hours to obtain the impurity-removed X-type molecular sieve, add the impurity-removed activated carbon and impurity-removed X-type molecular sieve into a grinder according to proportion, grind for 1.5 hours, and grind to 300 mesh to obtain preliminary material mixture one.
[0080] Preparation of material mixture: preheat the oxazoline homopolymer to 55°C and keep it warm for 2 hours, then slowly add the preheated oxazoline homopolymer to preliminary material mixture one, stir and mix thoroughly to obtain preliminary material mixture two, the stirring speed is 1000r / min, the stirring temperature is 70°C, the stirring time is 2.3h, and the material mixture is obtained by hot air drying at an ambient temperature of 100°C for 5 hours to remove moisture.
[0081] Preparation of PHA composition: polyhydroxyalkanoate, filler mixture and material mixture are added into a twin-screw extruder from the main feed port in proportion for melt mixing, and a rheology modifier is added to the feeding side of the extruder to improve the material processing performance, and the melt extruded from the die is cooled and pelletized to obtain the desired PHA composition, wherein the extruder barrel temperature is set to 150°C and the extruder speed is 300rpm.
[0082] Comparative Example 1
[0083] The invention provides a low-odor PHA composition with high paper-plastic composite strength and a preparation method thereof. The low-odor PHA composition with high paper-plastic composite strength comprises the following components by weight: 100 parts by weight of polyhydroxyalkanoate, 55 parts by weight of filler, 25 parts by weight of polymer-containing material, 5 parts by weight of coupling agent, 4 parts by weight of rheology modifier, 6 parts by weight of cellulase, 4 parts by weight of pectinase, and 150 parts by weight of distilled water. The specific preparation method of the low-odor PHA composition with high paper-plastic composite strength comprises the following steps:
[0084] Preparation of filler mixture: Clean wood fiber, bamboo fiber, flax fiber and jute fiber with pure water, drain the water, air-dry for 3 hours at an ambient temperature of 25°C, chop wood fiber, bamboo fiber, flax fiber and jute fiber respectively, mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber evenly in proportion to obtain a preliminary filler mixture, add the preliminary filler mixture and distilled water to a sand mill in proportion, mix, beat and grind for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat to 55°C, and stir at 600r / min for 3 hours to obtain a mixed solution 2, add the mixed solution 2 and a coupling agent to a reaction container in proportion to obtain a mixed solution 3, then heat the mixed solution 3 to 100°C and keep it warm for 6 hours to obtain a mixed solution 4, spread the mixed solution 4 on a tray, put it in an oven, and dry it for 4 hours at an ambient temperature of 60°C to obtain a filler mixture.
[0085] Preparation of preliminary material mixture one: Add activated carbon and distilled water into a reaction vessel, heat to 100°C and keep warm for 2 hours, then cool for 2 hours and cool to 25°C and drain the water, dry for 1.5 hours to obtain impurity-removed activated carbon, wash the X-type molecular sieve with distilled water, then drain the water and dry for 1.3 hours to obtain the impurity-removed X-type molecular sieve, add the impurity-removed activated carbon and impurity-removed X-type molecular sieve into a grinder according to proportion, grind for 1.5 hours, and grind to 300 mesh to obtain preliminary material mixture one.
[0086] Preparation of material mixture: preheat the oxazoline homopolymer to 55°C and keep it warm for 2 hours, then slowly add the preheated oxazoline homopolymer to preliminary material mixture one, stir and mix thoroughly to obtain preliminary material mixture two, the stirring speed is 1000r / min, the stirring temperature is 70°C, the stirring time is 2.3h, and the material mixture is obtained by hot air drying at an ambient temperature of 100°C for 5 hours to remove moisture.
[0087] Preparation of PHA composition: polyhydroxyalkanoate, filler mixture and material mixture are added into a twin-screw extruder from the main feed port in proportion for melt mixing, and a rheology modifier is added to the feeding side of the extruder to improve the material processing performance, and the melt extruded from the die is cooled and pelletized to obtain the desired PHA composition, wherein the extruder barrel temperature is set to 150°C and the extruder speed is 300rpm.
[0088] Comparative Example 2
[0089] The invention provides a low-odor PHA composition with high paper-plastic composite strength and a preparation method thereof. The low-odor PHA composition with high paper-plastic composite strength comprises the following components by weight: 100 parts by weight of polyhydroxyalkanoate, 55 parts by weight of filler, 25 parts by weight of polymer-containing material, 5 parts by weight of coupling agent, 6 parts by weight of hydrochloric acid, 4 parts by weight of rheology modifier, and 150 parts by weight of distilled water. The specific preparation method of the low-odor PHA composition with high paper-plastic composite strength comprises the following steps:
[0090] Preparation of filler mixture: Clean wood fiber, bamboo fiber, flax fiber and jute fiber with pure water, drain the water, air-dry for 3 hours at an ambient temperature of 25°C, chop wood fiber, bamboo fiber, flax fiber and jute fiber respectively, mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber evenly in proportion to obtain a preliminary filler mixture, add the preliminary filler mixture and distilled water to a sand mill in proportion, mix, beat and grind for a period of time to obtain a mixed solution 1, add the mixed solution 1 and a coupling agent to a reaction container in proportion to obtain a mixed solution 2, slowly add hydrochloric acid to the mixed solution 2 while stirring, the stirring speed is 700r / min, the preset target pH value is 3.5, use a pH meter to monitor the pH value of the mixed solution 2, when the pH value of the mixed solution 2 reaches the target pH value, stop adding hydrochloric acid, heat to 100°C and keep warm for 6 hours to obtain a mixed solution 3, spread the mixed solution 3 on a tray, put it in an oven, and dry it for 4 hours at an ambient temperature of 60°C to obtain a filler mixture.
[0091] Preparation of preliminary material mixture one: Add activated carbon and distilled water into a reaction vessel, heat to 100°C and keep warm for 2 hours, then cool for 2 hours and cool to 25°C and drain the water, dry for 1.5 hours to obtain impurity-removed activated carbon, wash the X-type molecular sieve with distilled water, then drain the water and dry for 1.3 hours to obtain the impurity-removed X-type molecular sieve, add the impurity-removed activated carbon and impurity-removed X-type molecular sieve into a grinder according to proportion, grind for 1.5 hours, and grind to 300 mesh to obtain preliminary material mixture one.
[0092] Preparation of material mixture: preheat the oxazoline homopolymer to 55°C and keep it warm for 2 hours, then slowly add the preheated oxazoline homopolymer to preliminary material mixture one, stir and mix thoroughly to obtain preliminary material mixture two, the stirring speed is 1000r / min, the stirring temperature is 70°C, the stirring time is 2.3h, and the material mixture is obtained by hot air drying at an ambient temperature of 100°C for 5 hours to remove moisture.
[0093] Preparation of PHA composition: polyhydroxyalkanoate, filler mixture and material mixture are added into a twin-screw extruder from the main feed port in proportion for melt mixing, and a rheology modifier is added to the feeding side of the extruder to improve the material processing performance, and the melt extruded from the die is cooled and pelletized to obtain the desired PHA composition, wherein the extruder barrel temperature is set to 150°C and the extruder speed is 300rpm.
[0094] Comparative Example 3
[0095] The invention provides a low-odor PHA composition with high paper-plastic composite strength and a preparation method thereof. The low-odor PHA composition with high paper-plastic composite strength comprises the following components by weight: 100 parts by weight of polyhydroxyalkanoate, 55 parts by weight of filler, 25 parts by weight of polymer-containing material, 5 parts by weight of coupling agent, 6 parts by weight of hydrochloric acid, 6 parts by weight of cellulase, 4 parts by weight of pectinase, and 150 parts by weight of distilled water. The specific preparation method of the low-odor PHA composition with high paper-plastic composite strength comprises the following steps:
[0096] Prepare a filler mixture: use pure water to clean wood fiber, bamboo fiber, flax fiber and jute fiber, drain the water, air-dry for 3 hours at an ambient temperature of 25°C, chop the wood fiber, bamboo fiber, flax fiber and jute fiber respectively, mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber in proportion to obtain a preliminary filler mixture, add the preliminary filler mixture and distilled water to a sand mill in proportion, mix and beat for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat to 55°C, and The mixture was stirred at a speed of 600 r / min for 3 h to obtain a mixed solution 2, the mixed solution 2 and the coupling agent were added into the reaction vessel in proportion to obtain a mixed solution 3, hydrochloric acid was slowly added into the mixed solution 3 while stirring, the stirring speed was 700 r / min, the preset target pH value was 3.5, and the pH value of the mixed solution 3 was monitored by a pH meter. When the pH value of the mixed solution 3 reached the target pH value, the addition of hydrochloric acid was stopped, the mixture was heated to 100°C and kept warm for 6 h to obtain a mixed solution 4, the mixed solution 4 was spread on a tray, put into an oven, and dried at a temperature of 60°C for 4 h to obtain a filler mixture.
[0097] Preparation of preliminary material mixture one: Add activated carbon and distilled water into a reaction vessel, heat to 100°C and keep warm for 2 hours, then cool for 2 hours and cool to 25°C and drain the water, dry for 1.5 hours to obtain impurity-removed activated carbon, wash the X-type molecular sieve with distilled water, then drain the water and dry for 1.3 hours to obtain the impurity-removed X-type molecular sieve, add the impurity-removed activated carbon and impurity-removed X-type molecular sieve into a grinder according to proportion, grind for 1.5 hours, and grind to 300 mesh to obtain preliminary material mixture one.
[0098] Preparation of material mixture: preheat the oxazoline homopolymer to 55°C and keep it warm for 2 hours, then slowly add the preheated oxazoline homopolymer to preliminary material mixture one, stir and mix thoroughly to obtain preliminary material mixture two, the stirring speed is 1000r / min, the stirring temperature is 70°C, the stirring time is 2.3h, and the material mixture is obtained by hot air drying at an ambient temperature of 100°C for 5 hours to remove moisture.
[0099] Preparation of PHA composition: polyhydroxyalkanoate, filler mixture and material mixture are added into a twin-screw extruder from the main feed port in proportion for melt mixing, and a rheology modifier is added to the feeding side of the extruder to improve the material processing performance, and the melt extruded from the die is cooled and pelletized to obtain the desired PHA composition, wherein the extruder barrel temperature is set to 150°C and the extruder speed is 300rpm.
[0100] Experimental example
[0101] The same paper cup base paper was coated with the PHA compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 to prepare paper cups. After hot water was poured into the paper cups, the odor intensity of the paper cups was analyzed:
[0102] 120 well-trained assessors aged between 20 and 30 years old, both male and female, with good sense of smell and no olfactory impairment, were selected and divided into 5 groups. The 5 groups of assessors were trained to ensure that they understood the purpose and method of the test.
[0103] The specific preparation steps of paper cups are:
[0104] Step 1: Load the base paper into the unwinding mechanism, and the laminating production line will pull the unwinding mechanism at high speed to feed the paper. During the unwinding process, the unwinding tension of the base paper is controlled to be 40kg / m. 2 ;
[0105] Step 2: performing corona treatment on the printing surface of the conveyed base paper, wherein the current of the corona treatment is 5A;
[0106] Step 3: The PHA compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention were respectively heated in the barrel of a twin-screw extruder and melt-extruded, wherein the barrel section temperature of the twin-screw extruder was 200° C., and the die section temperature was 320° C., to form a PHA composition film with a thickness of 620 μm.
[0107] Step 4: The printed surface of the base paper conveyed at high speed is then laminated with the PHA composition film via a high-speed laminating roller to obtain a coated paper, and the pressure of the laminating roller is 120 kg / m;
[0108] Step 5: Use a circulating water cooling device to cool the coated paper, and the temperature of the cooling water is 15°C;
[0109] Step 6: Transport the cooled coated paper to the winding mechanism to form a coated paper roll. During the winding process, the winding tension of the coated paper is controlled to be 30kg / m. 2 ;
[0110] Step 7: Use a die-cutting machine to cut the coated paper into fan-shaped pieces required for making paper cups, put the die-cut fan-shaped paper pieces into a paper cup forming machine, and form the shape of the paper cup through mechanical action.
[0111] Ensure that the laboratory environment is clean and free from external odor or noise interference. Under the environmental conditions of temperature 20±2°C and humidity 60±5%, pour 90°C hot water into the paper cups after coating with the PHA compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3. Ask the assessors to smell the paper cups poured with 90°C hot water respectively, and record the intensity and characteristics of the odor, and record the evaluation results of the five groups respectively.
[0112] The statistical results are shown in Table 1:
[0113] Table 1:
[0114]
[0115] According to the data in Table 1, it can be seen that: Referring to Examples 1, 2, and 3, it can be seen that the filler component added in the preparation of the PHA composition is increased or decreased within the prescribed component range. The PHA compositions prepared using Examples 1, 2, and 3 are respectively coated on the same paper cups, and the odor does not change significantly after pouring hot water. Referring to Example 1 and Comparative Example 1, when the additives are the same and the additive mass components are the same, the pH value is not adjusted. The PHA composition prepared using Comparative Example 1 is coated on the same paper cup, and after pouring hot water, it will emit a slight pungent odor. Referring to Example 1 and Comparative Example 2, when the additives are the same and the additive mass components are the same, no enzymatic reaction is performed. The PHA composition prepared using Comparative Example 2 is coated on the same paper cup, and after pouring hot water, it will emit a significant pungent odor. Referring to Example 1 and Comparative Example 3, when the additives are the same and the additive mass components are the same, no rheology modifier is added. The PHA composition prepared using Comparative Example 3 is coated on the same paper cup, and after pouring hot water, it will emit a slight pungent odor.
[0116] Test the bonding strength between paper cup and coating layer:
[0117] The paper cups prepared by the above method were used to measure the bonding strength between the paper cups and the coating layer according to the method described in GB / T 34444-2017.
[0118] Table 2 shows the specific test results:
[0119] Table 2
[0120] sample Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Peel strength 1.55N / mm 1.52N / mm 1.52N / mm 0.95N / mm 1.05N / mm 1.15N / mm
[0121] According to the data in Table 2, it can be seen that, with reference to Examples 1, 2, and 3, the filler component added in the preparation of the PHA composition is increased or decreased within the specified component range. The PHA compositions prepared in Examples 1, 2, and 3 are respectively coated on the same paper cups, and the bonding strength between the paper cups and the coating layer does not change significantly. With reference to Example 1 and Comparative Example 1, when the additives are the same and the additive mass components are the same, the pH value is not adjusted. When the PHA composition prepared in Comparative Example 1 is coated on the same paper cup, the bonding strength between the paper cup and the coating layer is reduced. With reference to Example 1 and Comparative Example 2, when the additives are the same and the additive mass components are the same, the enzymatic reaction is not performed. When the PHA composition prepared in Comparative Example 2 is coated on the same paper cup, the bonding strength between the paper cup and the coating layer is reduced. With reference to Example 1 and Comparative Example 3, when the additives are the same and the additive mass components are the same, the rheology modifier is not added. When the PHA composition prepared in Comparative Example 3 is coated on the same paper cup, the bonding strength between the paper cup and the coating layer is reduced.
[0122] It can be seen that the PHA composition prepared by the present invention is added with natural fiber as filler, which can not only reduce costs and absorb irritating odors, but also improve the biodegradability and environmental performance of the material, improve the thermal stability and UV resistance of the prepared PHA composition, and the addition of polymer-containing materials can improve the water resistance of the PHA composition, improve its mechanical properties and processing properties, and the addition of rheology modifiers can improve the compatibility of PHA with other polymers, thereby achieving better performance in the blend, improving the fluidity and printing accuracy of the filled composite material, and the PHA composition as a coating layer not only has low irritating odor and low impact on the environment, but also has high paper-plastic composite strength.
[0123] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A PHA composition with low odor and high paper-plastic composite strength, characterized in that: According to the weight of the components, the low-odor and high-paper-plastic composite PHA composition includes the following components: 95-120 parts by weight of polyhydroxyalkanoate, 40-80 parts by weight of filler, 5-80 parts by weight of polymer-containing material, 5-10 parts by weight of coupling agent, 5-25 parts by weight of hydrochloric acid, 4-10 parts by weight of rheology modifier, 5-10 parts by weight of cellulase, 3-10 parts by weight of pectinase, and 80-180 parts by weight of distilled water; The filler comprises one or a mixture of two or more of wood fiber, bamboo fiber, flax fiber and jute fiber; The polymer-containing material includes one or a mixture of two or more of activated carbon, X-type molecular sieve and oxazoline homopolymer; The coupling agent is specifically vinyltrimethoxysilane; The polyhydroxyalkanoate is poly 3-hydroxybutyrate co-3-hydroxyhexanoate; The rheology modifier includes one or a mixture of two or more of xanthan gum, agar gum, polyurethane, epoxy resin, polyethylene glycol, glycerol and triacetin.
2. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 1, characterized in that: The processing methods include: Step 1: Preliminary treatment of fillers: clean wood fiber, bamboo fiber, flax fiber and jute fiber with purified water, drain the water, and after air-drying for a period of time, chop the wood fiber, bamboo fiber, flax fiber and jute fiber respectively, and mix the chopped wood fiber, bamboo fiber, flax fiber and jute fiber in proportion to obtain a preliminary filler mixture; Step 2, enzymatic hydrolysis of filler: add the preliminary filler mixture and distilled water to a sand mill in proportion, mix, beat and grind for a period of time to obtain a mixed solution 1, add the mixed solution 1, cellulase and pectinase to a blender in proportion, heat and stir for a period of time to obtain a mixed solution 2; Step 3, filler modification reaction: Add the mixed solution 2 and the coupling agent into a reaction container in proportion to obtain a mixed solution 3, slowly add hydrochloric acid to the mixed solution 3 while stirring, preset a target pH value, and use a pH meter to monitor the pH value of the mixed solution 3. When the pH value of the mixed solution 3 reaches the target pH value, stop adding hydrochloric acid, heat and keep warm for a period of time to obtain a mixed solution 4; Step 4, preparing a filler mixture: spreading the mixed solution 4 on a tray, and placing it in an oven to dry for a period of time to prepare a filler mixture; Step 5: Preliminary treatment of polymer-containing materials: Add activated carbon and distilled water into a reaction vessel, heat to boiling and keep warm for a period of time, then cool for a period of time and drain the water, and dry for a period of time to obtain impurity-removed activated carbon; The X-type molecular sieve is washed with distilled water, and then the water is drained and dried for a period of time to obtain the impurity-removed X-type molecular sieve; Add impurity-removing activated carbon and impurity-removing X-type molecular sieve into a grinder according to a certain proportion and grind for a period of time to obtain a preliminary material mixture 1; Step 6, preparing a material mixture: preheating the oxazoline homopolymer and keeping it warm, then slowly adding the preheated oxazoline homopolymer to the preliminary material mixture 1, stirring and mixing thoroughly to prepare the preliminary material mixture 2, and drying by hot air drying for a period of time to remove moisture to prepare the material mixture; Step 7, preparing the PHA composition: adding the polyhydroxyalkanoate, filler mixture and material mixture into the twin-screw extruder from the main feed port in proportion for melt mixing, and adding a rheology modifier to the feeding side of the extruder to improve the material processing performance, and cooling and pelletizing the melt extruded from the die to obtain the desired PHA composition.
3. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 2, characterized in that: In the step 1, the air-drying time is 3 hours and the air-drying temperature is 25-50° C.; In the step 1, the mass ratio of wood fiber, bamboo fiber, flax fiber and jute fiber is 20:1-20:1.5-15:0.1-12:
12.
4. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 2, characterized in that: The mass ratio of the preliminary filler mixture to distilled water in step 2 is 20:1-50; In the step 2, the mass ratio of the mixed solution 1, cellulase and pectinase is 50:1-5:1-5; In the step 2, the stirring speed is 500-700 r / min, the temperature of the enzymatic hydrolysis reaction is 40-70° C., and the time of the enzymatic hydrolysis reaction is 2-24 h.
5. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 2, characterized in that: In the step 3, the mass ratio of the mixed solution 2 to the coupling agent is 20:0.1-5; In the step 3, the preset target pH value is 3.5, and the stirring speed is 600-800 r / min; In the step 3, the temperature is heated to 80-100° C. and kept warm for 5-8 hours.
6. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 2, characterized in that: In the step 4, the drying temperature is 50-80° C. and the drying time is 3-24 hours.
7. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 2, characterized in that: In the step 5, the activated carbon is heated to 100° C. and kept warm for 0.5 to 2 hours, then cooled for 1 to 2.5 hours, cooled to a temperature of 20 to 35° C., and dried for 0.5 to 2 hours; Dry the washed X-type molecular sieve in step 5 for 1 to 3 hours; In the step 5, the mass ratio of the impurity-removing activated carbon to the impurity-removing X-type molecular sieve is 3-12:7-20, and the grinding is performed for 0.1-2.5 hours until the mixture is ground to 300 meshes.
8. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 2, characterized in that: In the step 6, the oxazoline homopolymer is preheated to 50-60° C. and kept warm for 1-2.5 hours; In step 6, the stirring speed is 800-1200 r / min, the stirring temperature is 50-80° C., and the stirring time is 0.5-3 h; Drying time is 1.5 to 5 hours, and the drying temperature is 80 to 120°C.
9. The method for preparing a PHA composition with low odor and high paper-plastic composite strength according to claim 2, characterized in that: In the step seven, the mass ratio of the polyhydroxyalkanoate, the filler mixture and the material mixture is 50:5-27:7-15, wherein the speed of the twin-screw extruder is 300 rpm and the temperature is 150°C.
